English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

Find the error in the following proof:
Given: a = b = 1
Prove: 1 = 0 (obviously false!)

Given:
a = b
Multiply:
a*a = a*b
(a^2 = ab)
Subtract:
a^2 - b^2 = ab - b^2
Factor:
(a+b)(a-b) = b(a-b)
Divide:
(a+b) = b
Subtract:
a = 0
Substitute:
1 = 0
Q.E.D.

2006-11-09 11:31:11 · 5 answers · asked by topher8128 2 in Science & Mathematics Mathematics

5 answers

you cannot divide by 0 = a-b
\

2006-11-09 12:09:57 · answer #1 · answered by lola l 1 · 2 1

The problem lies when you divide by a-b which can not be done since you can not divide 0.

2006-11-09 19:42:39 · answer #2 · answered by kevt007 2 · 0 0

Fallacy is when u divide eq. by a-b
becacuse a=b
so a-b=0
thus u cannot divide eq by 0

2006-11-09 19:36:44 · answer #3 · answered by Dupinder jeet kaur k 2 · 0 0

The error is here:

(a+b)(a-b) = b(a-b)
Divide:
(a+b) = b

You are basically dividing by zero. That's a no-no.

2006-11-11 17:39:51 · answer #4 · answered by Dr. J. 6 · 0 0

you cannot divide by 0
in this case a-b=0

2006-11-10 12:28:24 · answer #5 · answered by locuaz 7 · 2 2

fedest.com, questions and answers